University Logo Recognition Application Design Using Template Matching Method - Pradana Putra, Gevin Janitto; Cahyadi Putra, I Gusti Ngurah Anom (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 9 No 2 (2020): JELIKU Volume 9 No 2, November 2020, 2020)
A logo is a special symbol or symbol that represents a company or organization. A logo can be a name, symbol or other graphic element that is displayed visually [1]. All institutions have a logo, especially an educational institution, namely the University, but the university logo is rarely remembered by lecturers, students, or the public. To be able to remind and provide information about the university, the university logo scan application which will later be directed to the university link is considered by the author suitable to be made. This kind of research has been tested with high accuracy but does not use the University logo. This research will utilize Augmented Reality program design with slight modifications and apply the Template Matching method that will be made with the Unity Game Engine and Vuforia SDK. This research was successful as evidenced by the smooth installation of APK and good program performance. In addition, this study obtained 84% accuracy in the detection of markers (logos) which were known by the distance and focus of the camera. This research also gets 100% accuracy in the direction to the intended university link. Keywords : Logo, University, Matching Templates, Vuforia SDK, Unity Game Engine